Neuronal activity patterns in the ventral thalamus: Comparison between Parkinson's disease and cervical dystonia. Issue 12 (December 2017) - Devetiarov, Dmitriy; Semenova, Ulia; Usova, Svetlana; Tomskiy, Alexey; Tyurnikov, Vladimir; Nizametdinova, Dinara; Gushcha, Artem; Belova, Elena; Sedov, Alexey
Highlights: The ventral thalamus was characterised by five common patterns in both PD and CD. There were no specific patterns or differences in distribution between PD and CD. Burst patterns and characteristics had an unbalanced distribution between PD and CD. Abstract: Objective: The aim of this study was to distinguish neuronal activity patterns in the human ventral thalamus and reveal common and disease-specific features in patients with Parkinson's disease (PD) and cervical dystonia (CD). Methods: Single unit activity of neurons was recorded during microelectrode-guided thalamotomies. We classified neurons of surgical target and surrounding area into patterns and compared their characteristics and responsiveness to voluntary movement between PD and CD patients. Results: We distinguished five patterns of neuronal activity: single, LTS burst, mixed, non-LTS burst and longburst patterns. The burst and mixed patterns showed significant differences in several basic and burst characteristics. We showed that there were no disease-specific patterns or significant differences in pattern distribution between studied patients. However, burst patterns had an unbalanced distribution between disease conditions. In addition, we found difference in LTS burst characteristics between surgical targets and surrounding nuclei. All identified patterns, except the long burst pattern, were reactive to the motor tasks and to contraction of the pathological muscles. Conclusions: The ventral thalamus was characterised by common neuronal activity patterns which differed in characteristics between PD and CD. Significance: Our findings highlight patterns of neuronal activity of the human ventral thalamus and specific pathological features.